Health Care Transition for Adolescents and Young Adults With Pediatric-Onset Liver Disease and Transplantation: A Position Paper by the North American Society of Pediatric Gastroenterology, Hepatology, and Nutrition. Issue 1 (13th January 2023) - Vittorio, Jennifer; Kosmach-Park, Beverly; King, Lindsay Y.; Fischer, Ryan; Fredericks, Emily M.; Ng, Vicky L.; Narang, Amrita; Rasmussen, Sara; Bucuvalas, John
Abstract : Advances in medical therapies and liver transplantation have resulted in a greater number of pediatric patients reaching young adulthood. However, there is an increased risk for medical complications and morbidity surrounding transfer from pediatric to adult hepatology and transplant services. Health care transition (HCT) is the process of moving from a child/family-centered model of care to an adult or patient-centered model of health care. Successful HCT requires a partnership between pediatric and adult providers across all disciplines resulting in a transition process that does not end at the time of transfer but continues throughout early adulthood. Joint consensus guidelines in collaboration with the American Society of Transplantation are presented to facilitate the adoption of a structured, multidisciplinary approach to transition planning utilizing The Six Core Elements of Health Care Transition TM for use by both pediatric and adult specialists. This paper provides guidance and seeks support for the implementation of an HCT program which spans across both pediatric and adult hepatology and transplant centers.